Association Between Patient Characteristics and Histopathological Features of Lung Cancer At RSUP Dr. Mohammad Hoesin Palembang - Isnani Nur I; Susilawati Susilawati; Soilia Fertilita (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Introduction. Lung cancer is the uncontrolled growth of malignant cells by the body in lung tissue and is caused by genetic mutations and changes in protein synthesis in normal cells. Histopathological features of lung cancer include squamous cell carcinoma, adenocarcinoma, small cell carcinoma, and other types. Early detection, as well as prevention, needs to be done in high-risk communities with the aim of reducing the number of events. This study aims to determine the relationship between sociodemographic factors and histopathological features of lung cancer. Methods. This study is an analytic observational study with a cross-sectional design. The research sample is in the form of secondary data from the Department of Anatomical Pathology and Medical Record Installation for 2019-2021. The research was conducted at Dr. Mohammad Hoesin Palembang. The sampling technique was carried out by total sampling. Results. Most of the respondents were in the age group >45 years (84.1%), male (78.3%), had no history of smoking (60.9%), the predominant main complaint was shortness of breath (63, 8%), the most common histopathological picture is adenocarcinoma. There was no significant relationship between age (p=0.998), gender (p=0.736), smoking history (p=0.572) and histopathological features of lung cancer patients. Conclusion. There was no significant relationship between age, sex and smoking status on the histopathological features of lung cancer.